Praktik Baik Pemerataan Akses Literasi Bagi Anak-Anak Pengidap HIV/AIDS Menggunakan Buku Cerita Tiga Dimensi Di Kota Surakarta - Prayoga, Afrizal Adi; Ricardo, Pradana (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stigmatization of children living with HIV/AIDS (ADHA) has led to discrimination against access to literacy for ADHA. Every child, including ADHA, needs literacy skills, especially language and culture. Therefore, good practices to equalize and improve literacy for ADHA, especially in the Yayasan Lentera Shelter House in Surakarta City, are needed. The service location was chosen in Surakarta City, with partner Yayasan Lentera, as an intensive place for ADHA. The service activities involved 25 ADHA participants aged 10-12 years from primary education. Facing community stigmatization of ADHA, the service team designed good practices for equal access to literacy using three-dimensional storybooks. The activity involved the participants' experience and understanding of Central Java folklore, with a pre-test on the Bledug Kuwu story. The service was carried out through three stages: filling in the pre-test, reading the folklore using a three-dimensional illustrated storybook, and post-test. The results showed a significant increase in ADHA's understanding and knowledge of Central Java folklore material presented through three-dimensional picture storybooks. This media is adequate because it can increase participants' focus while strengthening language and cultural literacy. Evaluation of the program's success refers to the participants' post-test results. The program successfully stimulated the interest and enthusiasm of participants, creating positive changes in ADHA literacy in Surakarta City.